2016
DOI: 10.11648/j.ajpn.20160402.11
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Produces Motor Incoordination and Hypoactivity in Infant Wistar Rats Through GABA<sub>A</sub> Receptors

Abstract: A mixture of eight fatty acids (linoleic, oleic, palmitic, stearic, myristic, elaidic, lauric, and palmitoleic acids) at similar concentrations that have been identified in human amniotic fluid exerts anxiolytic-like effects similar to diazepam in adult Wistar rats through actions at γ-aminobutyric acid-A (GABA A) receptors, but unknown is whether any of these fatty acids exerts a predominant action over the others in infant rats. Of these fatty acids, some actions of oleic acid have already been identified, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In the present study, the DZP-5 group had the smallest number of total crossings (H 4 = 11.214, p = 0.024) and the smallest number of crossings in the central zone (H 4 = 10.067, p = 0.039) compared to other groups (control, DZP-0.1, DZP-0.5, and DZP-1; Table I). This hypoactivity illustrates a seda- tive effect of 5 mg kg -1 diazepam, an effect consistent with a previous study that found that the 5 mg kg -1 dose increased sedation scores in PND28 rats (11). This finding in the DZP-5 group suggests that 5 mg kg -1 should not be administered in weaning rats because it is sedative rather than anxiolytic.…”
Section: Diazepam Dose-response Studysupporting
confidence: 90%
“…In the present study, the DZP-5 group had the smallest number of total crossings (H 4 = 11.214, p = 0.024) and the smallest number of crossings in the central zone (H 4 = 10.067, p = 0.039) compared to other groups (control, DZP-0.1, DZP-0.5, and DZP-1; Table I). This hypoactivity illustrates a seda- tive effect of 5 mg kg -1 diazepam, an effect consistent with a previous study that found that the 5 mg kg -1 dose increased sedation scores in PND28 rats (11). This finding in the DZP-5 group suggests that 5 mg kg -1 should not be administered in weaning rats because it is sedative rather than anxiolytic.…”
Section: Diazepam Dose-response Studysupporting
confidence: 90%
“…Diazepam (Valium 10, Hoffman-Roche, Basel, Switzerland) was used as the reference anxiolytic drug and injected intraperitoneally at a dose of 1 mg/kg dissolved in isotonic saline solution (v2) in a volume of 1 ml/300 g. This dose was selected because it produces anxiolytic-like effects in 28-day-old rats [ 19 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, many studies reported that the alteration of α5 GABAAR levels have been observed in neurodevelopmental disorders [77,78]. Additionally, down-regulation of Gabra1, 3 and 5 mRNA levels was reported in Alzheimer's disease (AD) patients [79]. In the present study, the expression level of three α subunit-encoding genes, Gabra1, Gabra3 and Gabra5, were evaluated in response to Topamax and ginger oil and their interaction.…”
Section: Discussionmentioning
confidence: 84%